2021
DOI: 10.1186/s12957-021-02239-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-MRI radiomics enables the prediction of preoperative cerebral spinal fluid dissemination in children with medulloblastoma

Abstract: Background Medulloblastoma (MB) is the most common pediatric embryonal tumor. Accurate identification of cerebral spinal fluid (CSF) dissemination is important in prognosis prediction. Both MRI of the central nervous system (CNS) and CSF cytology will appear false positive and negative. Our objective was to investigate the added value of preoperative-enhanced T1-weighted image-based radiomic features to clinical characteristics in predicting preoperative CSF dissemination for children with MB. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Pre-operative identification of the molecular subgroup of medulloblastoma is extremely important as the extent of resection depends on the molecular subtype [56]. Therefore, Thompson et al [57] analyzed the prognostic value of the extent of resection in a retrospective multi-institutional cohort involving 787 patients with medulloblastoma. Only in group 4 tumors, wide neurosurgical resection was associated with a significant increase in progression-free survival, but not in overall survival.…”
Section: Pediatric Brain Tumorsmentioning
confidence: 99%
“…Pre-operative identification of the molecular subgroup of medulloblastoma is extremely important as the extent of resection depends on the molecular subtype [56]. Therefore, Thompson et al [57] analyzed the prognostic value of the extent of resection in a retrospective multi-institutional cohort involving 787 patients with medulloblastoma. Only in group 4 tumors, wide neurosurgical resection was associated with a significant increase in progression-free survival, but not in overall survival.…”
Section: Pediatric Brain Tumorsmentioning
confidence: 99%
“…The latter is of paramount importance, as it would assist with further understanding of the diverse nature of MBs and the designation of appropriate treatment strategies. Until recently, radiomic analysis had managed to indirectly predict the prognosis of patients, as MRI findings were associated with the molecular subgroup of the tumor [58,59] or the dissemination to the CSF [60]. However, the co-estimation of imaging findings, clinical characteristics, and molecular subgroup led to the development of nomograms, predicting both PFS [61] and OS [62].…”
Section: Other Prognostic Factorsmentioning
confidence: 99%
“… 19 In MB patients, Zheng et al found a clinical-radiomic model to be predictive of preoperative Cerebrospinal Fluid (CSF) dissemination (as determined by head and spine MRI, as well as no subsequent dissemination at the 1-year follow-up for the non-CSF dissemination group). 33 …”
Section: Summary Of Radiomics Studies In Pediatric Neuro-oncologymentioning
confidence: 99%
“…Some authors noted that moving forward, multicenter data could be used to increase sample size and evaluate model generalizability. 32 , 33 There exist a few consortiums to facilitate data collection and sharing, 41 , 42 such as the Children’s Brain Tumor Network , which has several cloud-based platforms, outlined in Figure 2 , where researchers can access the data. Other databases relevant for radiomic studies include the National Cancer Institute’s Clinical Proteomic Tumor Analysis Consortium (CPTAC) and the Pediatric Brain Tumor Consortium.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%